2012
DOI: 10.1519/jsc.0b013e31821e4d5b
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Strength and Power Qualities Over Two Years in Volleyball Players Transitioning From Junior to Senior National Team

Abstract: The purpose of this investigation was to examine the changes in performance indicators as they relate to strength and speed-strength development, over 2 years in a group of volleyball players who successfully transitioned from age group (U21) to senior national team in that time period. Sixteen male subjects (age: 18.5 ± 1.5 years, height: 2.00 ± 0.06 m, and weight: 88.4 ± 7.7 kg) participated in this 2-year longitudinal study. During the 24-month period of this investigation, all the subjects gained professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 7 publications
2
33
0
Order By: Relevance
“…In sports where relative strength is of importance, training should be aimed at increasing strength and power, while maintaining very low fat mass to reduce stress placed on the musculoskeletal system [23]. The combination of greater body mass, and reduced skin fold thickness, could lead to similar or faster sprint times, leading to greater momentum, which is likely to result in an increase in impact force during collisions, in turn increasing the difficulty for an opponent to stop or tackle the player.…”
Section: Citation: Thomas C Mather D Comfort P (2014) Changes In Spmentioning
confidence: 99%
See 3 more Smart Citations
“…In sports where relative strength is of importance, training should be aimed at increasing strength and power, while maintaining very low fat mass to reduce stress placed on the musculoskeletal system [23]. The combination of greater body mass, and reduced skin fold thickness, could lead to similar or faster sprint times, leading to greater momentum, which is likely to result in an increase in impact force during collisions, in turn increasing the difficulty for an opponent to stop or tackle the player.…”
Section: Citation: Thomas C Mather D Comfort P (2014) Changes In Spmentioning
confidence: 99%
“…National level softball athletes have shown to increase peak velocity and peak power in the jump squats, as well as increases in absolute and relative lower body strength through pre-, mid-and post-season performance testing whilst partaking in a periodized resistance training programme [22]. Sheppard et al [23] found changes in jump, and strength performance over two years in volleyball players as they transitioned from junior to senior national playing level. Little scientific evidence, however, exists regarding the magnitude of change in performance measures that can be expected over a long-term period in lacrosse players.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The isokinetic method is one of the methods which are used the most frequently to assess the strength capacity of the groups of muscles which act on the knee joint and evaluate the function of the knee joint after injuries have been sustained [14,15,16,17]. Such studies have involved, among others, the members of the national teams of Brazil [8], Spain [18], and Australia [10,19], as well as league players [5,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%